The Urgency Of Da'wah Activities In Mass Media - Mujiati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The development of technological progress currently being experienced has brought changes in various aspects of human life, especially in terms of access to information. Today's modern society tends to rely on mass media as the main source to meet their information needs. Mass media is considered more practical, fast and efficient, including in providing information about their religion. People only need to sit in front of various types of media such as the internet, radio, newspapers and television, and all their information needs can be met. The aim of this research is none other than to find out the urgency of preaching in the mass media, which is caused by the power of the mass media. The method used in this research uses research that focuses on reviewing literature/research libraries, using two data which includes primary data and secondary data. The results of this research show that da'wah activities carried out in the mass media are very important. This is because mass media has an important role in life. This important role includes a wide reach, being able to provide a broader understanding of religion, empowering the community, responding quickly, forming opinions. So that the da'wah messages conveyed by the preachers will be much more effective than traditional da'wah delivery such as pulpits, majlis ta'lim, and so on.